Finding Nearest Mosque Using Haversine Formula on Android Platform - Indah Setyorini; Desi Ramayanti (Department of Informatics, UIN Sunan Gunung Djati Bandung, 2019)
Prayer is the second pillar of Islam and it is emphasized after the two sentences of syahadat. It has been said that it’s as perfect and as good as worship. Prayer is one of the obligations for Muslims and must be done both for Mukimin and Musafir. The virtue of prayer in the mosque is the same as the value of 20 degrees of reward compared to prayer elsewhere. With the traffic jam phenomenon that is increasing due to heavy traffic. For someone who is traveling home in the afternoon before maghrib, some people are always confused to do Maghrib prayer because of the lack of information about the nearest mosque. The problem can be solved by finding the shortest path is a problem to find the minimum route from the starting point to the destination point with the shortest route. This research was made to design an application that provides direction to the nearest mosque in the area of Larangan, Tangerang city. In the making of this system to find the shortest path can be solved using the haversine formula and using the java programming language, where java is used to build applications while the database used is the MySQL database and the use of Google Maps API in determining the route.